2008
DOI: 10.1111/j.1600-6143.2008.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Cardiovascular Screening in Potential Renal Transplant Recipients: Single-Center Prospective Observational Study

Abstract: We assessed the outcome of pretransplant cardiac assessment in a single center. Three hundred patients with end-stage renal disease underwent electrocardiogram, Bruce exercise testing (ETT) and ventricular assessment by cardiac MRI. Patients with high index of suspicion of coronary artery disease (CAD) underwent coronary angiography and percutaneous coronary intervention (PCI) if indicated. Two hundred and twentytwo patients were accepted onto the renal transplant waiting list; 80 patients were transplanted du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 16 publications
(20 reference statements)
2
97
0
2
Order By: Relevance
“…This significantly impacts the cardiac assessment of potential renal transplant recipients and how to manage coronary artery lesions that are identified. A recent prospective study in a Scottish CKD population challenged the current practice of coronary angiographic screening (24). The authors reported no direct evidence of patient benefit from cardiac screening, and in fact suggested that it may serve as a barrier to being placed on a waiting list.…”
Section: Discussionmentioning
confidence: 99%
“…This significantly impacts the cardiac assessment of potential renal transplant recipients and how to manage coronary artery lesions that are identified. A recent prospective study in a Scottish CKD population challenged the current practice of coronary angiographic screening (24). The authors reported no direct evidence of patient benefit from cardiac screening, and in fact suggested that it may serve as a barrier to being placed on a waiting list.…”
Section: Discussionmentioning
confidence: 99%
“…A baseline transthoracic echocardiogram performed at dry weight is also important because it can help identify impaired LVEF and wall motion abnormalities, which may be signs of prognostically significant CAD 26. A normal cardiac stress test has a high negative predictive value for cardiovascular events27, 28 in the perioperative and follow‐up periods, as shown in a study of renal transplant candidates undergoing preoperative SPECT 29. A hybrid SPECT/computed tomography scan assesses for ischemia and coronary artery calcification, which is highly prevalent in patients with ESRD 30.…”
Section: Cad In Patients With Esrdmentioning
confidence: 99%
“…Since 2002 (10,11,13), we have used CMR as part of the standard assessment of patients for renal transplantation. The renal transplant unit at the Western Infirmary (Glasgow, Scotland, UK) provides transplant services to a population of 2.8 million people in the west of Scotland.…”
Section: Patientsmentioning
confidence: 99%